Maternal genetic variation of Betawi population - Wolly Candramila; Bambang Suryobroto (Tropical Genetics, 2021)
Betawi identity was assessed based on the diversity of maternal lines using genetic markers in the D-loop region of mitochondrial DNA. The results of the cleavage by the restriction enzymes DdeI, HaeII, HaeIII, and HinfI showed five patterns of genetic variants which were later named Haplotype I, II, III, IV, and V. Haplotype I had the highest frequency of 75.6%, followed by Haplotype III 11.5%, and Haplotype II 10.3%. Haplotypes IV and V were only found in 1 individual each and were assumed to be individual mutations. The highest haplotype in the Betawi population showed the same restriction enzyme cleavage pattern with all comparison samples from the Sunda and Malay populations. Meanwhile, Haplotype II and III were strongly suspected as the result of the divergence of Haplotype I and can also be found in other ethnic groups in Indonesia. This finding confirms Jakarta as a location for ethnic mixing which then produces a new local culture as Betawi Culture.